Estrategia metodológica intercultural ñukanchik pachamamata kuyankapak para preservar la relación armónica entre el hombre y la naturaleza. - Rivadeneira Peñafiel, Andrea Elizabeth (2018)
The research work intercultural methodological strategy ÑUKANCHIK PACHAMAMATA KUYANKAPAK to preserve the harmonic relationship between man and nature, is a pedagogical, didactic and intercultural tool that is based on the critical thinking of several authors. It arises from the evidence of the problematic evidenced, the same that lies in the fact that the students subject of study claim not to maintain a harmonious relationship with nature, demonstrating in them attitudes that reflect their scarce environmental awareness, since they feel unmotivated and little attracted to address issues of environmental education, since this subject has gone into the background in their educational training and do not practice habits to maintain an environmental balance. The main objective of this research was to propose an intercultural methodological strategy that helps to preserve the harmonic relationship between man and nature, and subsequently to base it theoretically, determine its components and validate it. The methodology used in the research is non-experimental, the design is qualitative, descriptive and explanatory. The population was 42 eighth-year students. To collect the information, the observer card was used as an observation technique with its respective instrument. For the analysis and interpretation of results we worked with the validation of experts, after that the triangulation of the information was performed, yielding 100% applicability results and a very satisfactory evaluation range. It was concluded that the proposal contributes to preserving the harmonious relationship between man and nature, since it addresses innovative issues, is an important tool with environmental content, seeks to link students directly with nature, its didactic structure has themes that will make a significant contribution to the sustainable development of Pachamama. Therefore, it is recommended to analyze and execute the proposal for strengthening and enrichment in the field of environmental education.